Cellular, molecular, and metabolic aspects of developing lungs in congenital diaphragmatic hernia - Perveen, Shahana; Frigeni, Marta; Benveniste, Helene; Kurepa, Dalibor (Frontiers in Pediatrics, 2022)
No abstract as it is a review article..